TRAINING TO IMPROVE SELECTIVE ATTENTION IN CHILDREN USING NEUROFEEDBACK THROUGH PLAY. - SAN LUIS, CONCEPCIÓN; LÓPEZ DE LA LLAVE, ANDRÉS; PÉREZ-LLANTADA, M. CARMEN (Revista de Psicopatologia y Psicologia Clinica)
This paper has two objectives: a) to identify if selective attention and concentration in school children without learning problems can be improved through training with neurofeedback; and b) to assess the generalizability of such training as a useful, easy, fun and economical procedure that may be used to improve school performance. For training we used Mind-Flex, a toy first marketed in 2009. To measure a possible boost in attention we applied the d2 test of attention developed by Brickenkamp (1962), adapted in Spain by Seisdedos (2002). The results obtained from a sample of 65 children (aged 8 and 9) show a significant improvement in selective and sustained attention, cognitive-processing accuracy, attention control and balance between speed and accuracy.